Physical activity, muscular strength, and polypharmacy among older multimorbid persons: Results from the KORA‐Age study. (12th April 2017) - Volaklis, K. A.; Thorand, B.; Peters, A.; Halle, M.; Heier, M.; Strasser, B.; Amann, U.; Ladwig, K. H.; Schulz, H.; Koenig, W.; Meisinger, C.
Abstract : The purpose of this study was to examine whether physical activity (PA) and muscular strength (MS) are related to polypharmacy. Our cross‐sectional analysis was based on 711 patients with multimorbidity (MMB), aged 65‐94 years, who participated in the KORA‐Age study. Participants underwent a face‐to‐face interview and extensive physical examinations including anthropometric measurements, registration of chronic diseases, determination of health‐related behaviors (smoking, alcohol intake, physical activity, etc.), collection of blood samples and measurement of hand‐grip strength. PPha was defined as the use of >4 drugs and MMB as having ≥2 of 13 chronic diseases. Prevalence of PPha was 44.6% (n=317), and a significant difference was found in the number of drugs used between participants with and without PPha (7.2±2.1 vs 2.5±1.2, P <.001). Patients in the lower compared to the upper tertile of physical activity had a significantly increased odds to be on PPha (OR: 1.64, 95% CI: 1.05‐2.56, P =.031) after controlling for age, gender, BMI, family status, education, alcohol intake, smoking habits, number of diseases, hs‐CRP, and telomere length. On the contrary, no significant association between muscular strength and PPha was found (OR: 1.04, 95% CI: 0.66‐1.63, P =.873) after multivariable adjustment. Among older persons with MMB, lower levels of physical activity, but not low muscular strength, are associated with higher odds of PPha. Increasing the levels of physical activity appears to be highly recommended in order to potentially reduce the risk of PPha among multimorbid persons aged 65 and older.